2004
DOI: 10.1136/ard.2003.011619
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of leptin in hypoandrogenicity in patients with systemic lupus erythematosus and rheumatoid arthritis

Abstract: Background: Hypoandrogenicity is common in obesity and in chronic inflammatory diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Adrenal androgens such as androstenedione (ASD) and dehydroepiandrosterone (DHEA) sulphate are low, which partly depends on the influence of TNF in chronic inflammatory diseases. Leptin is stimulated by TNF and is associated with hypoandrogenicity in non-inflammatory conditions. Objective: To study the interrelation between serum levels of leptin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 51 publications
2
25
0
3
Order By: Relevance
“…Harle et al showed that leptin might provide an important link between chronic inflammation and the hypoandrogenic state in SLE patients. 63 Higher leptin concentrations in SLE patients, with respect to controls, have been reported by different authors, [64][65][66] suggesting a relationship between leptin and lupus disease-correlated factors. The same data have been recently reported in Korean SLE patients.…”
Section: Leptin and Systemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…Harle et al showed that leptin might provide an important link between chronic inflammation and the hypoandrogenic state in SLE patients. 63 Higher leptin concentrations in SLE patients, with respect to controls, have been reported by different authors, [64][65][66] suggesting a relationship between leptin and lupus disease-correlated factors. The same data have been recently reported in Korean SLE patients.…”
Section: Leptin and Systemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…Leptin has been found to correlate negatively with adrenal androgen concentrations in patients with systemic lupus erythematosus and RA, suggesting that leptin may be an important link between chronic inflammation and the hypoandrogenic state. 155 Obesity and musculoskeletal disease A Anandacoomarasamy et al…”
Section: Connective Tissue Disordersmentioning
confidence: 99%
“…Hypoandrogenicity in males is common in obesity and in chronic inflammatory conditions such as systemic lupus erythematosus and RA. 155 Leptin, as well reflecting adipose tissue mass, is stimulated by tumor necrosis factor and is associated with hypoandrogenicity in non-inflammatory conditions. Leptin has been found to correlate negatively with adrenal androgen concentrations in patients with systemic lupus erythematosus and RA, suggesting that leptin may be an important link between chronic inflammation and the hypoandrogenic state.…”
Section: Connective Tissue Disordersmentioning
confidence: 99%
“…Low leptin levels associated with food restriction have been linked to CD4ϩ lymphocyte hyporeactivity and increased interleukin-4 (IL-4) secretion (35). Moreover, leptin has been involved in RA-induced hypoandrogenicity, since leptin levels were negatively correlated to androstenedione (36). Therefore, since leptin acts as a proinflammatory agent and androgens are generally considered as antiinflammatory molecules, the preponderance of leptin and hypoandrogenicity may help to perpetuate chronic rheumatic diseases such as RA.…”
Section: Leptin and Rheumatic Diseasesmentioning
confidence: 99%
“…Indeed, in a lupus animal model, both high-fat diet and leptin increase proinflammatory highdensity lipoproteins scores, atherosclerosis, and proteinuria, suggesting that factors typically associated with the metabolic syndrome can accelerate the disease and its cardiovascular complications (56). Moreover, leptin has been involved in SLE-induced hypoandrogenicity, since leptin levels were negatively correlated with androstenedione (36). In contrast to these studies, other groups have reported lower or unchanged circulating leptin levels in SLE patients compared to healthy controls (57,58).…”
Section: Adipokines In Rheumatic Diseases and Cardiovascular Complicamentioning
confidence: 99%